The Role of Trehalose 6-Phosphate in Crop Yield and Resilience. Issue 1 (28th March 2018) - Paul, Matthew J.; Gonzalez-Uriarte, Asier; Griffiths, Cara A.; Hassani-Pak, Keywan
Abstract : T6P can be targeted through genetic and chemical methods for crop yield improvements in different environments through the effect of T6P on carbon allocation and biosynthetic pathways.